A new class of supramolecular ligands stabilizes 14-3-3 protein–protein interactions by up to two orders of magnitude. Issue 1 (5th December 2018) - Gigante, A.; Grad, J.-N.; Briels, J.; Bartel, M.; Hoffmann, D.; Ottmann, C.; Schmuck, C.
Abstract : Identification of novel non-natural supramolecular ligands as stabilizers of 14-3-3ζ protein–protein interactions. Abstract : We report the first supramolecular stabilizers of the interaction between 14-3-3ζ and two of its effectors, Tau and C-Raf, which are involved in neurodegenerative diseases and proliferative signal transduction, respectively. These supramolecular ligands open up an opportunity to modulate functions of 14-3-3 with these effectors.